Analisis Segmentasi Pasar Dalam Pembelian Produk Minarako Padang Untuk Menentukan Target Pasar - Vajri Rahman, Ahmad (Riset Sinergi Indonesia, 2023)
Market segmentation is an important strategy in developing marketing programs, in this case marketing Minarko Padang products can help marketers meet consumer needs and desires appropriately. The aim of this research is to find out how to segment the Minarko Padang market so that it is appropriate to determine the target market. The research design used is descriptive. With a population of 50 respondents, the number of consumer samples was taken using a purposive sampling technique. The instrument used was a questionnaire sheet for Minarko visitors including name, age, gender, education and occupation. Data analysis uses descriptive analysis. The results of the research show that the demographic segmentation of Minarko consumers is mostly 18-28 years old, 22 people, while based on gender, it is almost equal between women and men, namely 28 women and 22 men, then based on education, the majority of respondents are educated. There were 12 students and 28 ex-students, based on work there were 10 respondents